Formulation of Formative Assessment Essays and Illustrations on Faith and Morals: Formulasi Asesmen Formatif Esai dan Bergambar pada Akidah Akhlak - Fatimah, Velly Desi Ayu; Khoeroni, Farid (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to determine the application of formative assessment to the creed and morals material, referring to Bloom's Taxonomy theory. This study uses a descriptive qualitative research method with data collection thru observation, interviews, field research, and literature review or online studies that support the research. The data analysis method was conducted using a descriptive analytical method thru data reduction, data presentation, and drawing conclusions. Specifically, although a number of previous studies have used essay-type questions, no study has been found that explicitly examines or develops question formats that incorporate images, such as visual matching questions. This indicates a research gap that is the main focus of this study. The research results indicate that the implementation of formative assessment in Akidah Akhlak learning materials using innovative methods or media and based on Bloom's Taxonomy theory is able to attract students' interest in maximizing the measurement of Akidah Akhlak learning outcomes. This allows for optimal and comprehensive assessment of students' learning outcomes across all aspects, as evidenced by the positive response from students after the trial implementation of innovative formative assessment forms based on Bloom's Taxonomy theory. The trial implementation of formative assessment using essay questions and image matching faced several obstacles, including time constraints, some students still showing a lack of focus by chatting, and the discovery of one student who did not yet have adequate reading skills.